Hierarchical CoFe oxyhydroxides nanosheets and Co2P nanoparticles grown on Ni foam for overall water splitting. (10th November 2020) - Duan, Ran; Li, Yejun; Gong, Shen; Tong, Yonggang; Li, Zhou; Qi, Weihong
Highlights: An efficient and feasible method is developed to synthesize CoFe-OOH@Co2 P electrocatalysts on Ni foams. The as-prepared CoFe-OOH@Co2 P/NF exhibited excellent activity and stability for oxygen evolution reaction (OER) and overall water splitting. The present work provides new insights on preparation of efficient electrocatalysts for overall water splitting. Abstract: The development of industrial application of water splitting demands simple and effective methods for the preparation of highly efficient electrocatalysts that are inexpensive and robust. Herein, we report a simple activation method to decorate 3D cobalt iron oxyhydroxide (CoFe-OOH) nanosheets on Co2 P nanoparticles with Ni foams (NF) as substrates. The synthesized catalysts exhibit excellent activity for electrochemical oxygen evolution reaction due to the hierarchical heterostructures and synergistic effects of CoFe-OOH and Co2 P. The as-prepared catalysts require a low overpotential of 199 mV to deliver 30 mA cm −2 in oxygen evolution reaction in 1 M KOH with a small Tafel slope of 39 mV dec −1, indicating favorable kinetics during electrolysis. The synthesized catalysts are further used as cathode and anode for overall water splitting, which only requires a cell voltage of 1.60 V at a current density of 30 mA cm −2 . This work provides new insights on the preparation of efficient electrocatalysts for overall water splitting, which may have the potentials for industrial water electrolysis. Graphical abstract: Image, graphical abstract